2010
DOI: 10.1242/dev.047894
|View full text |Cite
|
Sign up to set email alerts
|

The ATP-dependent chromatin remodeling enzyme CHD7 regulates pro-neural gene expression and neurogenesis in the inner ear

Abstract: SUMMARYInner ear neurogenesis is positively regulated by the pro-neural bHLH transcription factors Ngn1 and NeuroD, but the factors that act upstream of this regulation are not well understood. Recent evidence in mouse and Drosophila suggests that neural development depends on proper chromatin remodeling, both for maintenance of neural stem cells and for proper neuronal differentiation. Here, we show that CHD7, an ATP-dependent chromatin remodeling enzyme mutated in human CHARGE syndrome, is necessary for prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(136 citation statements)
references
References 55 publications
4
132
0
Order By: Relevance
“…By E13.5, reporter expression was found throughout the otic lines are used. The most commonly used line is the depending on the strength of the fluorescent reporter COX ET.AL: Conditional Gene Expression in the Mouse Inner Ear Using Cre-loxP Pirvola et al 2002;Arnold et al 2006;Zelarayan et al 2007;Barrionuevo et al 2008;Jones et al 2008;Rickheit et al 2008;Grimsley-Myers et al 2009;Schultz et al 2009;Wang et al 2009;Yamamoto et al 2009;Deng et al 2010;Freyer and Morrow 2010;Haugas et al 2010;Hurd et al 2010;Hwang et al 2010;Sipe and Lu 2011 (Hebert and McConnell 2000), which has been reported to cause haploinsufficiency phenotypes that include proliferation in other organs (Shen et al 2006;Eagleson et al 2007;Siegenthaler et al 2008). However, no change in proliferation in the inner ear has been reported in several papers where proper controls of Foxg1-Cre mice (without the floxed allele) were used (Yamamoto et al 2009(Yamamoto et al , 2011Hartman et al 2010;Brown and Epstein 2011).…”
Section: Cre/creer Lines For the Developing Otic Vesicle And Otocystmentioning
confidence: 99%
“…By E13.5, reporter expression was found throughout the otic lines are used. The most commonly used line is the depending on the strength of the fluorescent reporter COX ET.AL: Conditional Gene Expression in the Mouse Inner Ear Using Cre-loxP Pirvola et al 2002;Arnold et al 2006;Zelarayan et al 2007;Barrionuevo et al 2008;Jones et al 2008;Rickheit et al 2008;Grimsley-Myers et al 2009;Schultz et al 2009;Wang et al 2009;Yamamoto et al 2009;Deng et al 2010;Freyer and Morrow 2010;Haugas et al 2010;Hurd et al 2010;Hwang et al 2010;Sipe and Lu 2011 (Hebert and McConnell 2000), which has been reported to cause haploinsufficiency phenotypes that include proliferation in other organs (Shen et al 2006;Eagleson et al 2007;Siegenthaler et al 2008). However, no change in proliferation in the inner ear has been reported in several papers where proper controls of Foxg1-Cre mice (without the floxed allele) were used (Yamamoto et al 2009(Yamamoto et al , 2011Hartman et al 2010;Brown and Epstein 2011).…”
Section: Cre/creer Lines For the Developing Otic Vesicle And Otocystmentioning
confidence: 99%
“…In a recent study, Chd7 was also shown to promote quiescence and maintenance of adult hippocampal neural stem cell populations [50]. Considering that Chd7 also promotes neural stem cell progenitor proliferation in the developing olfactory and otic placodes [51,52], these studies provide convincing evidence that CHD7 is essential for stem cell function in a variety of tissues. However, the precise mechanisms by which CHD7 regulates stem cell proliferation, quiescence, fate, or differentiation, which binding partners and genomic targets it associates with, and whether these mechanisms vary between developmental and postnatal stages remain to be determined.…”
Section: Chd Proteins and Neural Stem Cellsmentioning
confidence: 77%
“…In each organ thus far analyzed, Chd7 expression has been predictive of tissue or cellular defects in mutant mice. In the inner ear, Chd7 heterozygous mice display hypoplasia or aplasia of the lateral and posterior semicircular canals and innervation defects of the vestibular sensory epithelium [52,59]. Conditional knockout of Chd7 causes complete aplasia of vestibular and cochlear structures, reductions in fibroblast growth factor signaling, and decreased proliferation with reduced otic neural progenitors and reduced expression of proneural genes such as Ngn1 and Neurod1 [52].…”
Section: Chd Proteins In Human Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…CHD7 and KMTD2 interact with members of the same chromatin remodeling machine and have common target genes (Butcher et al, 2017;Schulz et al, 2014;Verhagen et al, 2014). TBX1 and CHD7 are both needed for normal PAA development, and CHD7 alters the expression of TBX1 in inner ear neurogenesis (Hurd, Poucher, Cheng, Raphael, & Martin, 2010;Randall et al, 2009). For EFTUD2 and ZEB2, only clinical overlap has been described so far (Luquetti et al, 2013;Wenger et al, 2014).…”
Section: Resultsmentioning
confidence: 99%